La formación universitaria en investigación aplicada y el contexto de la complejidad: Una perspectiva estratégica para la innovación en ingeniería - Astorne, Renzo (2014)
How to approach higher education for training in applied research in a "change of epoch" where knowledge has become a substantial asset to the generation of value in goods and services in organizations? What strategy should be implemented when its efficiency tends to be measured through mechanisms external to the research areas of the university? Two questions that allow, on the one hand, going the traditional way in which the university reiterates trivial mechanisms for engineering research training, and, on the other, the holistic -systemic-cybernetic- approach that promotes this same training in the context of complexity. This paper reviews the experience in the field of engineering, emphasizing the educational strategy aimed at achieving an insight of knowledge, where the university is facing increasing difficulty in setting the direction of the areas of applied research in engineering and associated training processes, i.e., in establishing the strategy.